STUDY OF THE BENTHIC INVERTEBRATE COMMUNITY IN AL-TAYEB RIVER, SOUTHERN IRAQ (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The current study included the diversity of the benthic invertebrate community in Al-Tayyib River / southern Iraq, in addition to some physical and chemical properties of the river water, for the period from the beginning of January 2022. Six stations were chosen to collect samples monthly. The results showed that the water temperature during the study period ranged (between 19-30) and the river water, salty, ranged between (5.1-6.14) ‰, while the pH values were neutral, ranging from (2.7-9) The study showed that the river water is well ventilated, as it recorded high values of dissolved oxygen, which ranged between (7-12 mg / liter). The river water became almost hard, so the total hardness values ranged between (725-5880 mg/l), and a total of 28,212 benthic invertebrates from all study stations and throughout the study period were distributed over nine taxonomic ranks, and crustaceans were dominated by 6,238 individuals, or 29% of the total number. Spatial and temporal variation in the distribution of species. The highest total number of benthic vertebrates , amounting to 1224 individuals. Shannon Weiner recorded high values for the diversity of invertebrates that ranged between 1.4-2.8 bits / individual. Jacquard's results showed that the strongest similarity relationship for benthic invertebrates amounted to 62%.